2023
DOI: 10.1002/alz.12969
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide methylomic regulation of multiscale gene networks in Alzheimer's disease

Abstract: INTRODUCTIONRecent studies revealed the association of abnormal methylomic changes with Alzheimer's disease (AD) but there is a lack of systematic study of the impact of methylomic alterations over the molecular networks underlying AD.METHODSWe profiled genome‐wide methylomic variations in the parahippocampal gyrus from 201 post mortem control, mild cognitive impaired, and AD brains.RESULTSWe identified 270 distinct differentially methylated regions (DMRs) associated with AD. We quantified the impact of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 136 publications
0
12
0
Order By: Relevance
“…Detailed clinical data, postmortem neuropathological data, and demographics of the cohort are described in. 29 We constructed gene co-expression and detected multiscale gene modules using MEGENA 30 on the differentially abundant excitatory neurons, which were identified as those neurons in control subjects most susceptible to neuronal loss in AD. Differential expression of genes between AD vs control was identified by the FinderMarkers function of the Seurat (v4.0) workflow 31 , using the MAST algorithm 32 .…”
Section: Double Label Immunohistochemistrymentioning
confidence: 99%
“…Detailed clinical data, postmortem neuropathological data, and demographics of the cohort are described in. 29 We constructed gene co-expression and detected multiscale gene modules using MEGENA 30 on the differentially abundant excitatory neurons, which were identified as those neurons in control subjects most susceptible to neuronal loss in AD. Differential expression of genes between AD vs control was identified by the FinderMarkers function of the Seurat (v4.0) workflow 31 , using the MAST algorithm 32 .…”
Section: Double Label Immunohistochemistrymentioning
confidence: 99%
“…We performed DEP analysis in AD vs NL over the proteomics profile in two human AD cohorts using the postmortem tissue from two different brain region: the parahippocampal gyrus (PHG) for the Mount Sinai Brain Bank (MSBB) 32 and the prefrontal cortex (PFC) for the Religious Orders Study and Memory and Rush Aging (ROSMAP) 52,53 cohort, respectively. The processing, normalization and co-variable adjustment for the human proteomics are as previously described 31 . In the present study, we stratified the subjects by sex and then identified the sex-specific DEPs in AD in comparison with NL (Supplementary Data 4).…”
Section: Sex-specific Dep Analysis In Human Cohortsmentioning
confidence: 99%
“…Gene co-expression networks on the proteomes in the human cohorts were identified by using Multiscale Embedded GEne co-expression Network Analysis (MEGENA) as described in 31,54 .…”
Section: Co-expression Network Analysismentioning
confidence: 99%
See 2 more Smart Citations